Dielectric Elastomer Generators: Recent Advances in Materials, Electronic Circuits, and Prototype Developments - IEUAN COLLINS (Advanced Energy and Sustainability Research, 2025)
The ongoing climate crisis requires innovative methods to maximize renewable and sustainable energy resources. There have been advancements in harvesting energy from ambient motions such as wind, ocean waves, and human movements. Dielectric elastomer generators (DEGs) are a promising option for energy harvesting due to their high energy density and compatibility with low-frequency oscillations. This review provides an in-depth overview of DEGs, including electroactive materials, electromechanical characterization, electronics for harvesting, interfacing circuits, prototypes, and challenges. DEGs have the potential to play a significant role in decarbonizing energy for both small and large-scale applications using ambient energy sources.